Pengaruh Kompetensi Instruktur, Perencanaan dan Implementasi Terhadap Kualitas Kompetensi Peserta Program Pelatihan Kerja pada Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Semarang - Umi Chasanah; Jefristson R Riwu Kore (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out and prove the influence of instructor competence, training planning, and training implementation on the quality of competency of participants in the job training program at the Semarang Vocational Training and Productivity Center (BBPVP). In this study, the quality of participant competence is the main indicator of the success of the training program. However, several factors such as instructor competence, proper training planning and implementation are often identified as important determinants influencing those outcomes. The research method used is a quantitative method with 100 samples from 912 populations. Data was collected from a number of trainees at BBPVP Semarang through validated questionnaires. The types of data sources used are primary and secondary data. The data analysis technique in this study uses SPSS (Statistical Product and Service Solution) software version 26. The results of this study show that the competence of instructors, training planning and training implementation significantly affect the quality of participants' competencies by 42.1%. These findings indicate the importance of improving the competence of instructors as well as planning and implementing more effective training to improve the quality of training results at BBPVP Semarang.